An investigation about teachers’ perception on Assessment Literacy and its Impact in Hindering the practice of effective Assessment in a Private School in Sharjah, UAE - Bourenane, Imane (2022)
Although assessment is said to be the core component for vital learning outcomes, there are many arguments about the efficiency of teachers planning effectively for it. Instead of using assessment primarily to improve learning, teachers are using it to only evaluate the students’ achievements. Many researchers have shown that assessment should be used as a tool to enhance learning and its results to be analyzed for that sake. In fact, teachers are not well trained on how to approach assessment in classes. Several studies have marked that teachers’ assessment skills are weak and need improvement either at the level of designing them or at the level of interpreting them. This study is an investigation of teachers’ perception of assessment literacy and its impact on effective assessment implementation. The data was collected through a mixed design questionnaire among 56 teachers with various years of experience in a private school in Sharjah. The participants were selected using a random sampling technique, and data were interpreted using descriptive statistics. The findings indicated that teachers have high assessment literacy; they use various traditional assessment tools to evaluate their students accordingly. However, the majority of teachers utilize assessment for the sake of judging the students’ achievements inside the classroom rather than improving the learning practices. In conclusion, one of the main reasons hindering practitioners in designing the appropriate assessment tool is the lack of training that the teachers should be equipped with.